2020
DOI: 10.1186/s13023-020-01357-0
|View full text |Cite
|
Sign up to set email alerts
|

2-methylacetoacetyl-coenzyme A thiolase (beta-ketothiolase) deficiency: one disease - two pathways

Abstract: Background: 2-methylacetoacetyl-coenzyme A thiolase deficiency (MATD; deficiency of mitochondrial acetoacetylcoenzyme A thiolase T2/ "beta-ketothiolase") is an autosomal recessive disorder of ketone body utilization and isoleucine degradation due to mutations in ACAT1. Methods: We performed a systematic literature search for all available clinical descriptions of patients with MATD. Two hundred forty-four patients were identified and included in this analysis. Clinical course and biochemical data are presented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…Fukao et al reported a 6year-old Japanese boy who was initially diagnosed with BKTD based on metabolic pro les, however, enzyme activity assays and mutation analysis nally con rmed the patient had HSD10MD [21]. Grunert et al recently described two patients who may actually have HSD10MD but were misdiagnosed as BKTD in earlier reports [1]. Thus the diagnosis of BKTD cannot be based solely on metabolite data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukao et al reported a 6year-old Japanese boy who was initially diagnosed with BKTD based on metabolic pro les, however, enzyme activity assays and mutation analysis nally con rmed the patient had HSD10MD [21]. Grunert et al recently described two patients who may actually have HSD10MD but were misdiagnosed as BKTD in earlier reports [1]. Thus the diagnosis of BKTD cannot be based solely on metabolite data.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-ketothiolase de ciency (BKTD, OMIM #203750) is an autosomal recessive disorder caused by a defect in mitochondrial acetoacetyl-CoA thiolase (T2, EC 2.3.1.9), affecting both isoleucine catabolism and ketolysis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-methylacetoacetyl-CoA thiolase (MAT; also known as β-ketothiolase, acetoacetyl-CoA thiolase, T2) deficiency results from pathogenic variants in ACAT1 , and is an organic aciduria involving defects in ketone body metabolism (ketolysis) and BCAA catabolism ( 90 ). MAT is involved in two metabolic pathways: (1) isoleucine catabolism, where it cleaves 2-methylacetoacetyl-CoA to propionyl-CoA and acetyl-CoA; (2) utilization of ketone bodies (ketolysis), cleaving acetoacetyl-CoA to acetyl-CoA ( 91 ). MAT deficiency was first described by Daum et al ( 92 ) as β-ketothiolase deficiency in a 6-year-old boy with severe metabolic acidosis and significant concentrations of the organic acids α-methyl-β-hydroxybutyric acid and α-methylacetoacetate in urine.…”
Section: Ketolytic/ketogenic Organic Acidemiasmentioning
confidence: 99%
“…It can present clinically similar to ketotic hypoglycaemia and succinyl-CoA:3-ketoacid CoA transferase (SCOT) deficiency (see next Section ), thus enzymatic diagnosis to confirm MAT deficiency is important ( 90 ). In total, 244 patients have been identified and reported thus far ( 91 ) but only one case had cardiac complications, an 8-year-old girl who died due to HF secondary to severe DCM ( 93 ).…”
Section: Ketolytic/ketogenic Organic Acidemiasmentioning
confidence: 99%